2020
DOI: 10.3390/microorganisms8060963
|View full text |Cite|
|
Sign up to set email alerts
|

Multiplexed High-Throughput Serological Assay for Human Enteroviruses

Abstract: Immunological assays detecting antibodies against enteroviruses typically use a single enterovirus serotype as antigen. This limits the ability of such assays to detect antibodies against different enterovirus types and to detect possible type-specific variation in antibody responses. We set out to develop a multiplexed assay for simultaneous detection of antibodies against multiple enterovirus and rhinovirus types encompassing all human infecting species. Seven recombinant VP1 proteins from enteroviruses EV-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…ELISA binding assays have previously been to test for the presence of cross-reactive anti-enterovirus antibodies in human polyclonal sera ( 16 19 , 26 , 40 42 ). Only EV-D68 was used in antibody neutralization assays in some of these studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ELISA binding assays have previously been to test for the presence of cross-reactive anti-enterovirus antibodies in human polyclonal sera ( 16 19 , 26 , 40 42 ). Only EV-D68 was used in antibody neutralization assays in some of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Results of studies examining both polyclonal human sera and a recombinant monoclonal antibody against the VP-4 capsid protein of EV-A71 suggest that antibodies against one genotype of EV-A71 can block infection of cells in culture by other genotypes and serotypes of the virus, as well as Coxsackievirus A16 and A6 ( 38 , 39 ). Antibody cross-reactivity among enteroviruses has also been observed using peptide arrays derived from the capsid proteins of multiple enteroviruses, including EV-D68, poliovirus type 1/Mahoney, Coxsackievirus A4 and B1, and human rhinoviruses ( 26 , 40 , 41 ). Whether or not cross-reactive antibodies can neutralize viruses of different enterovirus species (e.g., EV-C and EV-D) has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation is the use of a synthetic common EV peptide instead of different EV antigens in individual antibody assays. However, because of the great number of different EVs, which have so far been demonstrated to be associated with T1D [ 40 ], our approach might even be more justified. This is also a strength of our study, as it allows comparing the summation of exposures to different EVs for controls and for participants with T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme-linked immunoassays are faster, but there is considerable cross-reactivity between non-neutralizing antibodies that target different enteroviruses ( 15 17 ) and the general population, which has high levels of antibodies ( 18 ) due to the high prevalence of different kinds of enteroviruses. However, in our previous studies, we have observed that the antibody responses toward viral envelope protein 1 (VP1) proteins are more cross-reactive in adults than in children ( 19 ). We have also shown that the antibody responses toward enterovirus nonstructural protein proteases 2A and 3C are potential markers of acute infection ( 20 ).…”
Section: Introductionmentioning
confidence: 99%